Studi Komparatif Operasional CRJ 1000 dan B 737-800 Rute CGK-BWX-CGK - Muhammad Widya Setiatama; Irwan Chairuddin; Vica Nurhayani Harahap (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
The aim in this study was to compare the level of efficiency and advantages of operating the Bombardier CRJ 1000 and Boeing 737-800 NG aircraft on the Jakarta-Banyuwangi-Jakarta route in order to face competition between airlines. Selection of aircraft types with a larger seat capacity is important to increase market share. However, it should be approved whether the technical operational takeoff weight, operational costs, and payload of the selected aircraft can generate optimum profit. Hence, the study is designed to solve these problems by using a comparative qualitative study with the research subjects being the airlines owned by the Government of the Republic of Indonesia and collecting secondary data from company documentation. Data analysis tools used are payload allowable calculation data based on aircraft structure and aircraft performance, as well as the BCG (Boston Consulting Group) matrix to determine the company's position in terms of market growth and market share. The results of this study indicate that the Bombardier CRJ 1000 aircraft has a small but efficient capacity, while the operation of the Boeing 737-800 NG incurs higher costs. However, with a large load capacity, the Boeing 737-800 NG can generate greater profits than the Bombardier CRJ 1000. Garuda Indonesia's position in the BCG matrix is in the star quadrant, with a relative market share value of 0.74 and an average market growth of 78.04.